Penguatan Karakter Bangsa Melalui Pendidikan Kewarganegaraan Di Era Digital - Eis Neli Bahiyah; Syamzaimar Syamzaimar (CV. SINAR HOWUHOWU, 2026)
Civic Education (PKn) plays a very strategic role in shaping the character of citizens who are Pancasila-spirited, democratic, and responsible. In the digital era marked by the rapid flow of information and the challenge of hoaxes, the urgency of PKn is increasing. This study aims to examine the strengthening of national character through Civic Education learning in the digital era for students at the Institut Sains Al-Qur'an Syekh Ibrahim Pasir Pangaraian. The method used is library research with a qualitative-descriptive approach. Data were collected from various library sources including books, journal articles, and official government documents. The results show that PKn can be an effective instrument in internalizing Pancasila values, strengthening national identity, and improving students' digital and critical literacy. The integration of technology in PKn learning has been proven to increase student engagement and the relevance of the material to contemporary issues. This research recommends that PKn be taught contextually by utilizing digital platforms, actual case studies, and value-based approaches rooted in Islamic values that characterize the institution.